Assessment of Biomass Dynamics and Structural Functional Attributes in West-Central Himalayan Forest Ecosystems - Sorangi, Bhawana; Yadava, Anil Kumar; Sharma, Subrat; Arun Kumar, R. (Indian Forester, 2024)
The study highlights significant disparities between Oak and Pine forests in the West-Central Himalayas, showcasing Oak forests higher species richness, tree density, biomass, and net primary productivity, emphasizing the need for informed conservation strategies. Notable differences were observed between Oak and Pine forests. Oak forests displayed higher species richness, with tree densities ranging from 12 to 624 trees/ha, surpassing those of Pine forests (2 to 810 trees/ha). Biomass assessments indicated Oak forests' superiority, boasting an average above-ground biomass of 326.35 t/ha, significantly greater than that of Pine forests (286.53 t/ha). Additionally, Oak forests exhibited higher net primary productivity (NPP), ranging from 10.28 to 23.07 t/ha/yr, contrasting with Pine forests' NPP values of 23.07 t/ha/yr. These findings underscore the critical importance of comprehending ecological dynamics to inform effective forest management and conservation strategies in the West-Central Himalayas.